Data capture in the 80's - M. Brighton (Communicare)
This paper argues that social and economic pressures plus the rapid development of electronic devices will, through the present decade. produce a significant shift from face to face interviewing at private addresses, towards centralised interviewing, postal surveys, telephone surveys, qualitative research and direct data capture via specialised event recorders. The advantages of postal and telephone surveys will come to be better appreciated, and improved techniques will be adopted in both. The use of increasingly sophisticated and cos: effective electronics equipment will at first extend and improve existing techniques of data capture, but by the end of this decade electronic developments will have brought about fundamental and permanent changes in the way data can be collected.Survey research data capture techniques are going to change dramatically in the next decade, but this change can be expected to come about as the result of any single development in facilities, fashion, or philosophy. In fact these techniques will come about gradually, as a result of the changing pattern of commercial incentives and disincentives that face the individual and corporate researcher. By far the biggest disincentive is going to be the increasing difficulty and cost of arranging traditional face-to-face interviews at the home of the respondent, plus a growing awareness of the technical disadvantages of this technique.